Project Based Learning (PjBL) Model in Improving Students' Ability to Design Thesis Proposals - Kuswanto; Irzal Anderson (Universitas Pendidikan Ganesha, 2024)
Students' ability to prepare research proposals is the target of learning research methodology. Applying the Project Based Learning (PjBL) model in Research Methodology learning seeks to provide students with direct experience in preparing research proposals. This research aims to determine the effectiveness of implementing the PjBL model in improving students' abilities in preparing research proposals. This research was conducted using an experimental method: a Pretest-Posttest Control Group Design. The research subjects were 2 classes studying the research methodology course of the PPKn FKIP Study Program at Jambi University (R01 and R02). Class R02 was used as the experimental class and R02 as the control class. The research data is in the form of an N-Gain score, namely a score for increasing the ability to design a thesis proposal after implementing the PjBL model. Data were analyzed using comparative statistical techniques and independent sample t-tests. The results of the analysis show that the PjBL Model is quite effective in learning Quantitative Research Methods because it can improve students' ability to prepare a thesis proposal that is greater than conventional methods. The implications of the results of this research for learning Quantitative Research Methodology by assigning students to create a project in the form of a research proposal will strengthen their conceptual understanding and ability to design research proposals if managed systematically based on the PjBL model.